(untitled) (Contemporary Journal of Social Science Review, 2024)
This study investigates the integration of blockchain technology into the Agile Software Testing Life Cycle (STLC) through the Blockchain Enhanced Testing System (BETS), aiming to enhance security, transparency, and collaboration within software testing processes. Employing a mixed-methods approach, the research incorporates both quantitative and qualitative analyses, including performance evaluations, user feedback, and controlled experimental setups comparing traditional and blockchain-based testing frameworks.